(3GdfbO GdLeGdj (B/s - (3QjTGQ, CfOQjgs; (3gfQjs ((3aQfSG(B;(3dHfGf (B:s (3GdeWHhYGJ GdLGeYjI HaQfSG(B;(3OGQ efThQGJ YhjOGJ ,s, 1974)
(3cJH dgPg GdWHYI GdYQHjI ebOeI NGUI h edMbG Mhd GdfbO GdLeGdj aj GdGOH GdYQHjs
Keywords: (3GdCOH GdYQHjs; (3GdfbOs; (3GdGOHs